2020
DOI: 10.1002/jcp.29525
|View full text |Cite
|
Sign up to set email alerts
|

CCL21/CCR7 interaction promotes EMT and enhances the stemness of OSCC via a JAK2/STAT3 signaling pathway

Abstract: Chemokines and their receptors show a strong relationship with poor clinical outcomes in various cancers. However, their underlying mechanisms remain to be fully elucidated. In our research, we found C-C chemokine receptor 7 (CCR7) and its ligand chemokine ligand 21 (CCL21) were abnormally abundant in oral squamous cell carcinoma (OSCC) tissues, and CCR7 expression was correlated with poor prognosis of OSCC. After exogenous CCL21 stimulation, epithelial-mesenchymal transition (EMT) was promoted in OSCC cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 45 publications
0
82
0
Order By: Relevance
“…Hypoxia [ 199 , 200 , 201 ] and prostaglandin E 2 (PGE 2 ) [ 202 , 203 ] increases the expression of CCR7 on a cancer cell ( Figure 4 ). CCR7 enhances proliferation [ 204 , 205 , 206 ] and stemness of cancer cells [ 207 , 208 , 209 ]. The activation of CCR7 increases angiogenesis by activating NF-κB and thus increases VEGF-A expression in esophageal squamous carcinoma cells [ 210 ].…”
Section: Ccr7 Ccl19 and Ccl21mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia [ 199 , 200 , 201 ] and prostaglandin E 2 (PGE 2 ) [ 202 , 203 ] increases the expression of CCR7 on a cancer cell ( Figure 4 ). CCR7 enhances proliferation [ 204 , 205 , 206 ] and stemness of cancer cells [ 207 , 208 , 209 ]. The activation of CCR7 increases angiogenesis by activating NF-κB and thus increases VEGF-A expression in esophageal squamous carcinoma cells [ 210 ].…”
Section: Ccr7 Ccl19 and Ccl21mentioning
confidence: 99%
“…These are growth factors responsible for lymphangiogenesis. The activation of CCR7 on a cancer cell causes EMT and migration of cancer cells [ 199 , 200 , 204 , 205 , 206 , 209 ]. In blood and lymphatic vessels CCR7 on cancer cells prevents anoikis [ 205 , 214 ].…”
Section: Ccr7 Ccl19 and Ccl21mentioning
confidence: 99%
“…Moreover, OCT4 induces the production of IL-24 through the STAT3 and NF-κB signaling pathways, which can confer radiotherapy resistance to breast cancer cells by inhibiting radiation-induced senescence (65). The recognition and combination of ligand chemokine ligand 21 (CCL21) and C-C chemokine receptor 7 (CCR7) increase the expression of pluripotency-related transcription factors and stem cell markers (such as OCT4, CD133, CD44) by activating the JAK2/STAT3 signaling pathway, thereby enhancing the invasion, migration, and tumorsphere formation of oral squamous cell carcinoma (100). In addition, the STAT3 or STAT5A plays an important role in glioblastoma, which can be verified by the expression of OCT4 (101).…”
Section: Signal Transducer and Activator Of Transcription Pathwaymentioning
confidence: 99%
“…Recent study suggested that CCR7/CCL21 interaction can promote the lymph node of OSCC directly [22]. And CCR7/CCL21 interaction could also enhance the EMT process and promote stemness of OSCC by activating JAK2/STAT3 signal pathway [23]. Therefore, CCR7 is quite associated with the progression of OSCC.…”
Section: Discussionmentioning
confidence: 99%